Importance of Financial Statement Analysis in Determining Financial Health of Supermarkets In Kenya - Ngarari, Evelyn Diana W. (University of Embu, 2019)
Healthy financial performance is important in ensuring the gomg concern of a business. Financial analysis in the retail sector (supermarkets in this case) is accepted as a major instrument in measuring the financial health of a business by academics, practitioners and regulators in detecting and preventing insolvency. Supermarkets are a popular shopping spot for residents in Kenya and it is important for management of these enterprises to monitor their financial health so as to ensure their continued operation. The purpose of this study was to establish the importance of financial statement analysis in measuring the financial health of supermarkets in Kenya. The total population consisted of all major licensed supermarkets in Kenya as at 31 51 December 2018. Since the population of study was small, there was no need of sampling hence the whole population was used for the study. The study adopted descriptive survey of supermarkets in Kenya with for focus on the supermarkets that have gone banktupt. Secondary data was collected from audited financial reports of the banks from 2014- 2018. Regression Analysis was conducted in order to establish the importance of financial statement analysis in measuring the financial health of supermarkets. The independent variables included profitability, liquidity, solvency and stability. The dependent variable was be financial health and was measured mainly by the Z-score. The findings from the study confirmed that financial statement analysis is important in establishing the financial health of a business so as to make important managerial decisions. The study also revealed that analysis of financial statements is important for owners and managers to make informed decisions and take preventive action. The main assumption of the study was that managers prepare financial statements in good faith to reflect a true and fair view of the company's performance. 'The study therefore suggests that analysis of financial statements of supermarkets should be conducted carefully mainly by managers, owners, investors and suppliers. It also recommends that financial statements be prepared Altmari's in a manner that will facilitate financial analysis.